2014
DOI: 10.1002/gcc.22218
|View full text |Cite
|
Sign up to set email alerts
|

Inference on germline BAP1 mutations and asbestos exposure from the analysis of familial and sporadic mesothelioma in a high‐risk area

Abstract: Inherited loss-of-function mutations in the BAP1 oncosuppressor gene are responsible for an inherited syndrome with predisposition to malignant mesothelioma (MM), uveal and keratinocytic melanoma, and other malignancies. Germline mutations that were inherited in an autosomal dominant fashion were identified in nine families with multiplex MM cases and 25 families with multiple melanoma, renal cell carcinoma, and other tumors. Germline mutations were also identified in sporadic MM cases, suggesting that germlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
66
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 37 publications
4
66
0
1
Order By: Relevance
“…IHC findings in three epithelioid MM cases (C-II-1, D-II-3, O-II-3) suggest that the loss of nuclear staining occurred via somatic mutation Page 10 of 19 (see Figure 1). BAP1 nuclear staining retained in one sarcomatoid MM (G-II-8) is in agreement with other studies reporting data of positive BAP1 staining on sarcomatoid MM [25] and on the absence of BAP1 mutation [9,10,18,19]. Considering all families with multiple cases of MM analyzed to date for BAP1 germline mutations (see Table 2), those described in the present study without a predisposing germline BAP1 mutation are similar to those reported by other investigators [9,10,19].…”
Section: Case D-ii-3) Somatic Mutations In Exonsupporting
confidence: 93%
See 4 more Smart Citations
“…IHC findings in three epithelioid MM cases (C-II-1, D-II-3, O-II-3) suggest that the loss of nuclear staining occurred via somatic mutation Page 10 of 19 (see Figure 1). BAP1 nuclear staining retained in one sarcomatoid MM (G-II-8) is in agreement with other studies reporting data of positive BAP1 staining on sarcomatoid MM [25] and on the absence of BAP1 mutation [9,10,18,19]. Considering all families with multiple cases of MM analyzed to date for BAP1 germline mutations (see Table 2), those described in the present study without a predisposing germline BAP1 mutation are similar to those reported by other investigators [9,10,19].…”
Section: Case D-ii-3) Somatic Mutations In Exonsupporting
confidence: 93%
“…Other families were examined as part of asbestos surveillance program [10]. Our families were actively searched based on the Italian Mesothelioma Registry, and detected because the proband (index case) and at least one blood-relative were diagnosed with MM according to the Registry available information.…”
Section: Case D-ii-3) Somatic Mutations In Exonmentioning
confidence: 99%
See 3 more Smart Citations